Development perspectives - Institute of Economic Growth (Delhi, 1988)
The Institute of Economic Growth organised a number of academic and other activities in celebration of its Silver Jubilee during 1983-84. One of these was a series of Lectures by distinguished scholars. Thirteen Lectures were delivered. Of these, twelve are included in the present publication which has been delayed due to unavoidable circumstances. Regrettably, one of the lecturers, Professor Raj Krishan, suddenly passed away in 1985, and we are not able to include the text of his. We are grateful to all the lecturers for having accepted our invitation and added distinction to our Silver Jubilee programme by their participation as special lecturers.
Keywords: Economic development-India